Case report: Anti-PLA2R positive membranous nephropathy associated with atezolizumab. Issue 1 (February 2023) - Oleas, Diana; Saurina, Ana
Background: Immunotherapy has transformed cancer treatment in advanced malignancies. Increased survival compared with the standard of care has made immunotherapy a fundamental component of oncotherapeutics. Immune checkpoint inhibitors (ICI) trigger a stimulus to kill cancer cells. Immune-related adverse events (irAEs), derived from its potent stimulus, affect diverse organs. Acute interstitial nephritis (AIN) is the most frequent kidney irAE. Glomerulopathies, although rare, constitute a more challenging diagnosis and treatment. Case presentation: A 72-year-old man with lung adenocarcinoma treated with Bevacizumab and Atezolizumab. During treatment, he developed nephrotic syndrome. A diagnosis of a phospholipase A2 receptor positive primary membranous nephropathy associated with atezolizumab was made. After failing to respond to steroid therapy, treatment with rituximab was the preferred option. Eight months after being treated with rituximab and 10 months after atezolizumab was stopped, the patient maintained preserved renal function and negativization of anti-PLA2R was achieved. Proteinuria declined to half of its initial value 5 months following anti-PLA2R negativization. Conclusion: Monitoring proteinuria as well as declining kidney function in patients being treated with ICI is a valuable measure to determine an indication for a timely kidney biopsy and treatment.